Thermochemical conversion of Chlorella spp. into biochar and its potential environmental applications / Yu Kai Ling - Yu , Kai Ling (2021)
Microalgae are the first photosynthetic life forms of primitive earth and were able to fix atmospheric carbon dioxide (CO2) with the help of sunlight, thus creating a major step in the evolution of terrestrial plants. Microalgae are receiving increased attention recently based on their applicability in biomass production and implications on carbon capture. The microalgal biomass can be converted to several green products such as biochar and bioethanol via thermochemical conversion for environmental utilization. Biochar can be produced through thermochemical processes such as conventional pyrolysis and wet torrefaction. Thus, this study aims to study the production of microalgal biochar and its by-product using thermochemical conversion as a green technology in approach for environmental utilization. The feasibility of microalgal biochar production by conventional pyrolysis as well as simultaneous production of biochar and bioethanol using advanced wet torrefaction are investigated. Then, the characterization of microalgal biochar produced is studied for potential utilization as alternative coal fuel. Finally, the additional application of microalgal biochar on the adsorption of dye pollutants for wastewater treatment is also analyzed. Microalgae Chlorella vulgaris FSP-E with maximum biomass productivity of 0.87 g L-1 day-1 showed a biochar yield of 26.9% accomplished by conventional slow pyrolysis. C. vulgaris FSP-E biochar showed an alkaline pH value with H/C and O/C atomic ratios that are beneficial for carbon sequestration and soil application. The higher heating value of 23.42 MJ/kg of microalgal biochar also possesses its value as alternative coal. Microalgal biochar consisted of large aggregates with irregular porosity showed potential characteristics in the adsorption study. Besides, the simultaneous production of biochar and bioethanol can also be carried out through wet torrefaction. Microwave-assisted acid hydrolysis pretreatment by wet torrefaction was employed on two indigenous microalgae, Chlorella vulgaris ESP-31 and Chlorella sp. GD with different biomass compositions. The highest biochar yields of 54.5% and 74.6% can be obtained from C. vulgaris ESP-31 and Chlorella sp. GD, respectively under the wet torrefaction condition with an improvement in the properties for fuel. Wet torrefaction showed the high char yield with potential alternative fuel properties by using lower energy expense compared to the conventional slow pyrolysis. The high total reducing sugar concentration obtained in the liquid hydrolysate after the acid hydrolysis pretreatment was able to achieve the highest ethanol yield of 0.0761 g ethanol/ g microalgae. In addition, the microalgal biochar showed additional feasible adsorption performances on methylene blue and Congo red dye uptake with optimization on parameters such as adsorbent dosage, pH, initial concentration and time for future wastewater treatment utilization. Thermochemical conversion of biomass to biochar from microalgae using both conventional slow pyrolysis and wet torrefaction showed a feasible green conversion technology for environmental utilization. With the co-production of high total reducing sugar in the liquid hydrolysate that can be utilized for bioethanol production and solid biochar as another value-added product. In summary, acid hydrolysis pretreatment using wet torrefaction can be one of the environmentally sustainable conversion technologies towards the future application of renewable energy production.